Grandfathering vs. auctioning in the EU ETS: an experimental study - Fernandes, M. Eduarda (2010)
The present paper is the first to simultaneously include rules and parameters that try to parallel the EU ETS in the laboratory. To study the adequacy of the institution chosen for the EU ETS is our goal as well as testing the impact of changing the initial allocation rule: auctioning instead of grandfathering, in two different experimental treatments. The use of auctions as a rule for the initial allocation method for CO2 emission permits, in the next stages of the EU ETS (European Union Emissions Trading Scheme) is a subject the European Commission and its Member-States are currently discussing and evaluating. This paper is the first to experimentally test the Ausubel (2004) auction for the case of CO2 emission permits in the EU ETS, a theoretically efficient dynamic design for multiple units with results equivalent to the Vickrey auction. Our experimental results suggest that the Ausubel auction does not allocate CO2 emission permits efficiently but at the end total abatement cost minimization is still achieved in the auctioning treatment. The importance of the secondary market, and its functioning rules, is highlighted in this experimental treatment. Moreover, we conclude efficiency is the same whether emission permits are initially auctioned or grandfathered.